Sintering paths and mechanisms of pure MgAl2O4 conventionally and microwave sintered. Issue 17 (1st December 2018) - Macaigne, Rodolphe; Marinel, Sylvain; Goeuriot, Dominique; Saunier, Sébastien
Abstract: In this paper, a comparative study between conventional and microwave sintering of pure spinel MgAl2 O4 is presented. The goal is to clarify and identify the possible microwave effects on densification and microstructure of the pure spinel. Sintering trajectories obtained for microwave and conventional sintering are similar and converge into a unique trajectory. Therefore, microwave processing does not refine the grain size of pure spinel. The dominant mechanism of initial and intermediate stages of sintering was determined from the shrinkage curves and sintering trajectory. It was shown that densification is mostly controlled by grain boundary diffusion for both processes. Porosity of microwave and conventionally sintered samples was also characterized by mercury porosimetry and BET analysis. The evolution of the open porosity and pore size distribution is the same whatsoever the process used. This work shows that microwave sintering does not differ that much from conventional sintering on pure MgAl2 O4 material.